2023
DOI: 10.3390/ani13071269
|View full text |Cite
|
Sign up to set email alerts
|

A Quieter Ocean: Experimentally Derived Differences in Attentive Responses of Tursiops truncatus to Anthropogenic Noise Playbacks before and during the COVID-19-Related Anthropause

Abstract: The effects of anthropogenic noise continue to threaten marine fauna, yet the impacts of human-produced sound on the broad aspects of cognition in marine mammals remain relatively understudied. The shutdown of non-essential activities due to the COVID-19-related anthropause created an opportunity to determine if reducing levels of oceanic anthropogenic noise on cetaceans affected processes of sensitization and habituation for common human-made sounds in an experimental setting. Dolphins at Dolphin Quest Bermud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…Conspeci c presence and proximity reduces cortisol levels and personal vigilance in other mammals, likely due to collective predator-avoidance efforts (73)(74)(75), and previous work on dwarf mongooses found dominants to be more reliable sentinels compared to subordinates, resulting in reduced personal vigilance of foragers (24). Yet, repeated exposure to a stimulus can result in a lessened response due to gradual desensitisation, increased tolerance or habituation (76,77), with experimental evidence that wildlife can habituate to chronic noise (78)(79)(80). Whilst our playback trials are unlikely to have provided su cient noise exposure for habituation, the study population inhabits a reserve situated along a busy road.…”
Section: Discussionmentioning
confidence: 98%
“…Conspeci c presence and proximity reduces cortisol levels and personal vigilance in other mammals, likely due to collective predator-avoidance efforts (73)(74)(75), and previous work on dwarf mongooses found dominants to be more reliable sentinels compared to subordinates, resulting in reduced personal vigilance of foragers (24). Yet, repeated exposure to a stimulus can result in a lessened response due to gradual desensitisation, increased tolerance or habituation (76,77), with experimental evidence that wildlife can habituate to chronic noise (78)(79)(80). Whilst our playback trials are unlikely to have provided su cient noise exposure for habituation, the study population inhabits a reserve situated along a busy road.…”
Section: Discussionmentioning
confidence: 98%
“…This may be achieved through both wild and managed-care playbacks to assess recognition and response in both populations [113,114]. Using similar techniques, responses to anthropogenic noise playbacks can be used to determine just how cetaceans in pools will react to noises they have never heard in the wild and, potentially, help prepare them through acoustic habituation [15,114].…”
Section: Recommendationsmentioning
confidence: 99%
“…Animals 2024, 14,335 3 of 26 that are human made, either as structures or as bodies of water separated somehow from the wider ocean (Figure 1). Pools differ from lagoons and sea pens/sanctuaries in that they require filtration, which can be noisy [15]. However, they are typically protected from many environmental hazards that are unavoidable with open exposure to the ocean (red tides, hurricanes, oil spills, anthropogenic ship noise, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an evaluation of activity budgets of bottlenose dolphins, time periods in which construction noise was present resulted in behavioral changes, such as significantly faster swimming as well as decreased performance in training sessions [ 14 ]. Recently, an assessment of the anthropause due to COVID-19 found that dolphins that had become habituated to the anthropogenic sounds related to marine activity (e.g., jetskis and cruise ships) prior to the anthropause were more sensitive to playbacks following the reintroduction of human recreational activity near their lagoon [ 48 ]. At the MMP, an around-the-clock hydrophone array records the soundscape of the San Diego Bay where dolphins are housed in natural sea water environments [ 49 ] and “weights” the sound by the mid-frequency (MF)-cetacean hearing curve [ 44 ].…”
Section: Monitoring Anthropogenic Sound Levelsmentioning
confidence: 99%